The effect of dental educational level in adults (18-25 years old) with crowded teeth on the plaque and gingival conditions - Saad S Gasgoos; Saher S Gasgoos; Neam R Al-Saleem (University of Mosul, College of Dentistry, 2005)
Abstract The aim of the present study was to evaluate the relation between crowding, plaque and gingival conditions according to the level of dental education of the Iraqi adults. The sample was divided primarily into two groups: The first group was collected from dental students whom dentally well educated, while the second group was collected from other population whom dentally non educated (industrialist). Each group was subdivided into two groups according to the presence or absence of crowding, so that four groups were obtained (educated participants with non crowded teeth, educated persons with crowded teeth, non educated participants with non crowded teeth and non educated participants with crowded teeth). The results of this study indicated that the dental educational level is positively affecting on the gingival health in both crowded and normal occlusion. However, regardless of the level of education, plaque accumulation and gingivitis are significantly higher in the crowded teeth sample.